Impedance matching study of surface dielectric barrier discharge plasma generator - Guangke Xu; Weiwei Zhang; Nan Wang; Guangtao Wang; Shaopu Yuan (Energy Reports, 2020)
The plasma produced by Dielectric Barrier Discharge (DBD) has a very important application in the field of aerodynamics. The plasma generator needs high-voltage and high-frequency power supply. Due to the existence of internal resistance of the power supply, the impedance characteristics of the generator do not match the power supply. The voltage at both ends of the generator is extremely low. Besides, due to the existence of reactive power, most of the energy transported by the power source is reflected, resulting in extremely low energy conversion efficiency of the power source. In the paper, the mechanism of DBD plasma generator is analysed and on the equivalent circuit is received. And then different frequency impedance characteristics of generator and impedance matching circuit by using LR and the LCR respectively is studied. The results show that the equivalent resistance of plasma generator on frequency change is not obvious. The generator is capacitive and tends to 0 with increasing frequency. When LR is matched, resistance increases with the frequency change is not big, and reactance increases gradually, but its value is small, in the range of nΩ. in general the plasma generator impedance is virtually pure resistive. When LCR is matched, the impedance characteristic gradually changes from the inductive to capacitive with the increase of frequency.
Keywords: 330; Dielectric barrier discharge (DBD); Impedance matching; LCR; LR